Enhancing styrene production: CFD analysis of a Pd-based membrane reactor to carry out ethylbenzene dehydrogenation - M. Khosravi; M. Jafari; K. Ghasemzadeh; A. Iulianelli (Fuel Processing Technology)
A two-dimensional symmetric CFD model was developed using COMSOL Multiphysics 5.2 to evaluate the performance of traditional reactors (TRs) and membrane reactors (MRs) in the catalytic dehydrogenation of ethylbenzene (EB). The model examined the influence of key operating parameters, including temperature, pressure, feed flow rate, and sweep gas-to-feed ratio, on EB conversion, styrene selectivity, and hydrogen flux. The results indicated higher reaction temperatures enhanced EB conversion but reduced styrene selectivity. Similarly, increasing the sweep gas-to-feed ratio improved EB conversion and hydrogen permeation, while higher pressure and weight hourly space velocity negatively affected EB conversion but improved styrene selectivity. All parameters, except pressure, showed a direct correlation with hydrogen flux. Compared to the TR, the MR demonstrated superior performance, achieving up to 96 % EB conversion, 95 % styrene selectivity, and pure hydrogen production. The MR exhibited a 12.5 % higher EB conversion and 36.5 % greater styrene selectivity than the TR. Moreover, integrating the catalytic membrane reactor (CMR) concept, which includes auxiliary benzene hydrogenation, further enhanced process efficiency, increasing EB conversion to 60.85 % and styrene selectivity to 96.68 %.Additionally, a 14.5 % rise in the concentration polarization coefficient was observed with an increased sweep gas-to-feed ratio, whereas a 3.09 % reduction occurred with higher weight hourly space velocity. Temperature and pressure increases led to 3.95 % and 3.80 % rises in the polarization coefficient, respectively. These findings underscore the advantages of MRs and CMRs over conventional TRs in improving conversion efficiency, selectivity, and hydrogen purity.